Photoresponsive Passive Micromixers Based on Spiropyran Size‐Tunable Hydrogels. Issue 1 (18th April 2017) - ter Schiphorst, Jeroen; Melpignano, Giuseppe G.; Amirabadi, Hossein Eslami; Houben, Menno H. J. M.; Bakker, Sterre; den Toonder, Jaap M. J.; Schenning, Albertus P. H. J.
Abstract: Microfluidic devices allow the manipulation of fluids down to the micrometer scale and are receiving a lot of attention for applications where low volumes and high throughputs are required. In these micro channels, laminar flow usually dominates, which requires long residence times of the fluids, limiting the flow speed and throughput. Here a switchable passive mixer has been developed to control mixing and to easily clean microchannels. The mixer is based on a photoresponsive spiropyran based hydrogel of which the dimensions can be tuned by changing the intensity of the light. The size‐tunable gels have been used to fabricate a passive slanted groove mixer that can be switched off by light allowing to change mixing of microfluidics to non‐mixed flows. These findings open new possibilities for multi‐purpose microfluidic devices where mixers and valves can be tuned by light. Abstract : Passive micromixers have proven their use in microfluidic systems, improving the mixing efficiency and allowing higher throughput. In this work, a spiropyran containing photoresponsive size‐tunable hydrogel‐based passive micromixer is fabricated, which is used as a passive micromixer, allowing switching from a mixed to a nonmixed fluid flow in a microchannel by light.